TEORI DAN MODEL PENGEMBANGAN KURIKULUM DI INDONESIA - Fiska, Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Curriculum development is always carried out by the world of education in accordance with the demands of technological developments and population dynamics carried out by an educational institution. Curriculum development is usually carried out by the Government in general, and by a school that wants to improve the quality of the educational institution itself. In curriculum development, what must be considered first is the terminology in the curriculum itself. According to Dakir in his book Curriculum Planning and Development states: